Exploring Underpinning of Outsourcing Success: A case of Multinational Automotive group in Malaysia - Latif, Kashif; Ismail, Mohd Nazari; Nazri, Mohammad; Nor, Mohd Roslan Mohd; Qureshi, Muhammad Imran (International Journal of Engineering and Technology, 2018)
This study explored underpinning of outsourcing success by analyzing different theories of outsourcing. This study is unique in its nature as it used interpretive paradigm to explore, analyze outsourcing success theatrically by comparing different phases of outsourcing, then the case of Boeing analyzed in the context of outsourcing and after that come up with real time case study of one big automotive group operating in Malaysia through using semi structured interview by developing and comparing themes of this study. This study figured out that cost reduction and efficiency can be attained by creating economies of scale, using and managing vendors appropriately with the combination of efficient strategic alliance.